MCDT : a reactive energy efficient data aggregation and topology control algorithm for wireless sensor networks - Naveen Rai (2017)
The deciding factor behind the scalability and stability of a sensor network is its ability to fetch information from maximum number of nodes before 80% of nodes die. Also, one of the major challenge in WSN is to optimize the energy consumption of the nodes to improve lifetime of the network. In this project, an energy efficient clustering and routing algorithm has been proposed to increase lifetime of the network and optimize the distribution of load. This would lead to an increase in Network life time along with improved stability. From the results, it was found that the proposed algorithm was efficient in increasing the network life time and the stability of the network significantly. The main objectives kept in mind while developing the proposed algorithm are:  To Increase the life time of the complete network.  To develop a well distributed, load balanced network by reducing the amount of energy dissipated by each cluster-head.  To Increase the network stability by increasing the number of rounds before the first node dies and delaying the death of the last node. To achieve the objectives mentioned above, distance and residual energy based approach was incorporated for the formation of the cluster heads. A two-level clustering hierarchy has been used to forward the data packets from the lower region to the upper region and finally to the base station. A reactive approach was adopted to reduce the number of transmissions amongst the network.